Pain here and now: physical pain impairs transcendence of psychological distance - Agerström, Jens (J Pain Res, 2019)
BACKGROUND: The ability to traverse psychological distance by going beyond the experienced reality of the self, here and now, is fundamental for effective human functioning. Yet, little is known about how physical pain affects transcendence of psychological distance. Using a construal level theory framework of psychological distance, the current research examines the hypothesis that pain impairs people’s ability to traverse any kind of psychological distance whether it be temporal, social, and spatial distance, or the hypothetical. METHODS: Using the cold pressor test, 151 participants participated in an experiment where they were either induced with acute pain (treatment group) or no pain (control group) while completing a battery of questions measuring to what extent their current thoughts were transcending psychological distance. RESULTS: The results were largely consistent with the hypothesis. Relative to the control group, pain induced participants showed significantly less transcendence of past temporal distance, social distance, spatial distance, and the hypothetical. Furthermore, greater self-reported pain intensity was significantly associated with less transcendence of temporal (past and future), social, and spatial distance. CONCLUSION: Physical pain impairs the ability to traverse psychological distance. The research has practical implications for the pain clinic and for pain-afflicted individuals in everyday life.